CORRELATION ANALYSIS AND BODY SIZE VARIATION ETAWAH CROSSBREED GOATS IN UMEJERO VILLAGE, BUSUNGBIU DISTRICT, BULELENG REGENCY - Dinata, Sang Nyoman Arya; Sampurna, I Putu; Nindhia, Tjokorda Sari; Susari, Ni Nyoman Werdi; Sukada, I Made; Gunawan, I Wayan Nico Fajar (Buletin Veteriner Udayana, 2025)
This study aims to map the correlation and variability of body circumference measurements in male and female Etawah Crossbreed (PE) goats with mature body age (8–12 months) in Umejero Village, Busungbiu District, Buleleng Regency. A total of 81 PE goats—44 males and 37 females—were measured. Data collection involved direct measurement of neck circumference, chest circumference, hip circumference, and front canon leg circumference. Data were analyzed using error-bar graphs, correlation tests, and biplot mapping with varimax rotation via SPSS software. The results showed that male goats generally had larger body circumferences than females, although the differences were not statistically significant. A positive correlation was found among neck, chest, and hip circumferences, while the front canon leg circumference showed no significant correlation with the other variables. The greatest variation was observed in the front canon leg circumference (vector norm 0.9871), whereas the neck circumference showed the least variation (vector norm 0.6033), indicating higher uniformity. The biplot mapping successfully classified individuals into four quadrants based on morphological similarities, with Quadrant I representing goats with optimal body dimensions. These findings serve as a useful reference for selecting productive and proportional PE goats, supporting breeding and livestock management strategies in local farming systems.